Ambulatory Assessment in Mental Health Research: Expert Consensus on Current Practices and Future Directions - Löchner, Johanna; Santangelo, Philip Samuel; Ansell, Emily; Bolger, Niall; Ebner-Priemer, Ulrich; Fried, Elko; Gawrilow, Caterina; Hamaker, Ellen; Hepp-Kieslich, Johanna; Kaurin, Aleksandra; Kirtley, Olivia J; Kubiak, Thomas; et al. (2025)
Ambulatory Assessment (AA) studies have proliferated in mental health science,promising unparalleled insights into the dynamic nature of mental health. Thehigh methodological heterogeneity of AA studies calls for the harmonization ofapproaches and the establishment of research standards. This expert consensusprovides an overview of best-practice recommendations to integrate AA in mentalhealth research. We queried 26 experts in the field in a Delphi-adapted process,resulting in recommendations regarding eight topics, encompassing method-ological considerations, technological advancements, and practical applications;interdisciplinary collaboration and personalized treatment approaches were recur-rent themes. By establishing standardized guidelines and best practices, thisexpert consensus serves as a resource for mental health scholars seeking to lever-age AA tools in research and practice. Ultimately, the integration of AA holdspromise for revolutionizing mental health care, fostering precision medicine, andimproving outcomes for individuals living with mental disorder
https://cris.fau.de/converis/publicweb/Publication/336310725
Keywords: Ambulatory Assessment; Ecological Momentary Assessment; ExperienceSampling Method; Guidelines; Delphi Method; Mental Health

Bridging acute and chronic stress effects on inflammation: protocol for a mixed-methods intensive longitudinal study - Seizer, Lennart; Pascher, Anja; Branz, Sonja; Schmitt, Nadine; Löchner, Johanna; Schuller, Björn W.; Rohleder, Nicolas; Renner, Tobias J. (BMC Psychology, 2025)
Acute stress triggers adaptive physiological responses—including transient increases in inflammatory cytokines—while chronic stress is associated with sustained inflammatory activity that may underlie the development of various disorders. Despite extensive research on each stress type individually, the transition and interaction between them remain underexplored. This study aims to address this gap by employing an intensive longitudinal measurement burst design. Healthy university students will be recruited and monitored over three one-week assessment bursts, spaced by three-month breaks. Participants will complete ecological momentary assessments four times daily, recording their emotional states, stress experiences, and daily incidents. Simultaneously, saliva samples will be collected at matching time points to measure biomarkers of immune and stress system activity. In addition, daily audio diaries will provide qualitative context through advanced speech analysis techniques. Data will be analyzed using a multi-level modeling approach to differentiate within-person dynamics from between-person variability, accounting for potential moderators. The findings are expected to shed light on how repeated acute stressors transition into chronic stress and how chronic stress burden may influence acute stress responses.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Ecologcial momentary assessment; Inflammation; Intensive longitudinal data; Psychoneuroimmunology; Stress

Digital interventions in mental health: An overview and future perspectives - Löchner, Johanna; Carlbring, Per; Schuller, Björn; Torous, John; Sander, Lasse Bosse (Internet Interventions, 2025)
As e-health offerings rapidly expand, they are transforming and challenging traditional mental health care systems globally, presenting both promising opportunities and significant risks. This article critically examines the potential and pitfalls of integrating digital technologies into mental health care, particularly in the realms of diagnosis, prevention, and treatment. It explores current advancements and evidence-based practices, and provides a vision for how future technologies can evolve responsibly to meet mental health needs. The article concludes with the TEQUILA framework, addressing essential elements and challenges for fostering a beneficial and ethical future. A responsible future for digital mental health requires building Trust by ensuring data privacy, security, and transparency in AI-driven decisions, along with Evidence-based and robust regulatory oversight to maintain Quality. Usability, design, usability tailored to diverse needs, and ethical alignment with users' Interests will all be essential, while Liability and Accreditation standards will safeguard accountability in this evolving landscape.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Artificial intelligence; Digital mental health; Future perspective; Implementation; Treatment and prevention

Large language models for mental health - Triantafyllopoulos, Andreas; Terhorst, Yannik; Tsangko, Iosif; Pokorny, Florian B.; Bartl-Pokorny, Katrin D.; Seizer, Lennart; Seizer, Lennart; Klein, Ayal; Chim, Jenny; Atzil-Slonim, Dana; Liakata, Maria; Buehner, Markus; et al. (2025)
Digital technologies have long been explored as a complement to standard procedure in mental health research and practice, ranging from the management of electronic health records to app-based interventions. The recent emergence of large language models (LLMs), both proprietary and open-source ones, represents a major new opportunity on that front. Yet there is still a divide between the community developing LLMs and the one which may benefit from them, thus hindering the beneficial translation of the technology into clinical use. This divide largely stems from the lack of a common language and understanding regarding the technology's inner workings, capabilities, and risks. Our narrative review attempts to bridge this gap by providing intuitive explanations behind the basic concepts related to contemporary LLM
https://cris.fau.de/converis/publicweb/Publication/336145585

Nonlinear and symptom specific associations between chronotype and depression - Seizer, Lennart; Martínez-Albert, Estefanía; Löchner, Johanna (Scientific Reports, 2024)
The chronotype of individuals has been found to be predictive of depression risk and associated with the severity of depression. However, since depression is a phenotypically heterogeneous disease, it seems improbable that chronotype plays a role in every instance of depression. This study investigates the association between the two, while considering possible symptom-specificity and non-linearity of the relationship, utilizing a large sample from the National Health and Nutrition Examination Survey (N = 5217; 54% female; Age: M = 52.65, SD = 18.76). Depression symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9), and chronotype was determined by calculating sleep midpoints. Further, we also explored the potential mediating role of systemic inflammation, measured by C-reactive protein (CRP) levels, in the chronotype-depression link. The findings substantiate previous research indicating late chronotypes to be associated with higher PHQ-9 sum scores, with a minimum in PHQ-9 at a sleep midpoint of 02:49. The study further differentiates between individual depression symptoms, uncovering varying patterns of association with chronotype. No significant effect of chronotype on levels of CRP was found, suggesting that the link between chronotype and depression symptoms may not be directly mediated and appears to be stable and independent from systemic inflammation. The study highlights the non-linear and symptom-specific nature of the chronotype-depression connection and suggests the need for further, longitudinal studies to elucidate causal mechanisms and potential mediators.
Created from Fastlane, Scopus look-up
Keywords: Chronotype; Depression; Inflammation; Sleep; Symptom